TREE SPECIES DIVERSITY, STRUCTURAL CHARACTERISTICS AND CARBON STOCK IN A ONE-HECTARE PLOT OF THE PROTECTION FOREST AREA IN WEST LAMPUNG REGENCY, INDONESIA - Nur Muhammad Heriyanto; Ismayadi Samsoedin; Kuswata Kartawinata (Reinwardtia, 2019)
HERIYANTO, N. M., SAMSOEDIN, I. & KARTAWINATA, K. 2018. Tree species diversity, structural characteristics and carbon stock in a one-hectare plot of the protection forest area in West Lampung Regency, Indonesia. Reinwardtia 18(1): 1‒18. — A study of species composition, structure and carbon stock in the lower montane forest in the Register 45B of the protection forest area in the Tri Budi Syukur District, Kebun Tebu Village, West Lampung Regency, Lampung Province was conducted in September 2016. The objective of the study was to undertake quantified measurements of floristic composition and structure of and carbon storage in the lower montane forest at 965 m asl in the protection forest area. A one hectare plot (100 m × 100 m) was established randomly. The plot was further divided into 25 subplots of 20 m × 20 m each to record trees. Quadrats of 5 m × 5 m for saplings and subquadrats of 2 m × 2 m for seedlings were nested in the tree subplots. We recorded 247 trees with diameter at breast height ≥ 10 cm representing 25 species and 19 families, with a total basal area of 59.14 m2. Overall including seedlings and saplings we recorded 31 species. The species richness was very low due to disturbances, and was the lowest compared to that of other forests in Sumatra, Kalimantan and Java. The dominant species in terms of importance values (IV) were Litsea cf. fulva (IV=77.02), Lithocarpus reinwardtii (IV=45.21) and Altingia excelsa (IV=26.95). Dominant species in seedling and sapling stages were Polyalthia lateriflora (IV=27.54) and Memecylon multiflorum (IV=41.58). Biomass and carbon stock of trees with DBH ≥ 10 cm was 50.87 ton/ha and 25.43 ton C/ha, respectively. Regeneration was poor. Structurally and floristically the forest was a developing disturbed forest and the composition will remain unchanged in many years to come. The successions leading to terminal communities similar to the original conditions would be very slow and should be assisted and enhanced by applying ecological restoration through planting tree species native to the site.